Impact of process parameters on dimensional accuracy of PolyJet 3D printed parts using grey Taguchi method - Aslani, Kyriaki-Evangelia; Korlos, Apostolos; Kechagias, John D.; Salonitis, Konstantinos (EDP Sciences, 2020)
In this study, the dimensional accuracy of parts fabricated with PolyJet 3D Printing Direct process is investigated. An L4 orthogonal array was utilized as the design of experiments, while the process parameters examined are layer thickness, build style and scale. A simple prototype was proposed and specified external and internal dimensions were measured using a digital vernier calliper. Grey-Taguchi method was applied for optimizing all dimensional measurements. The effect of each parameter on dimensional accuracy has been identified using ANOM (Analysis of Means), while ANOVA (Analysis of Variances) has been performed to determine each parameter’s dominance. Additionally, the results of this study were compared with the findings of a previous optimization study in which the usual Taguchi method was used. It was concluded that 16 μm of layer thickness, glossy style and 50% scale provide the optimum dimensional results, while scale is the most important factor
Keywords: Grey-Taguchi method; PolyJet 3D Printing Direct process